PENINGKATAN PENGETAHUAN DAN KETERAMPILAN PENANGANAN CEDERA TUNGKAI DENGAN METODE PRICE DI SANGGAR TARI PEMATANGSIANTAR - I Ngurah Gede Verar Fujastawan; Isa Harpika Br. Ginting; Yeni Trisna Purba; Vicktor Henry Rony Apituley (Nusantara Hasana Journal, 2025)
This study aims to evaluate and improve the knowledge and skills for handling lower limb injuries using the PRICE method (Protection, Rest, Ice, Compression, Elevation) among training participants organized at Sanggar Tari Pematangsiantar. The PRICE method is proven effective in reducing swelling, alleviating pain, and accelerating the recovery process for acute injuries. Through an intensive one-day training, 35 participants from the local art and athletic communities underwent a series of theoretical sessions, technical practice, and simulated injury management. Evaluation was conducted using pre-test and post-test assessments, participatory observation, and visual documentation. The results demonstrated a significant improvement in both theoretical understanding and practical skills in applying the PRICE method. These findings indicate that community service training with a structured methodological approach can effectively enhance awareness and capability in injury management within art and sports communities